Comparison of match outcomes between the pool and final stages of the Japan rugby top league - Yamamoto, T.; Sasaki, K.; Murakami, J.; Watanabe, I.; Shimozono, H.; Chiba, G. (13th World Congress of Performance Analysis of Sport and 13th International Symposium on Computer Science in Sport. IACSS&ISPAS 2022, 2023)
This study discusses the influence of tournament stages on match outcomes. Eighty matches were analyzed from the 2018 Japan Rugby Top League, including fifty-six pool matches and twenty-four matches in the final stage. U and chi-square tests were used to identify the differences between stages (pool vs. final) by match outcomes and breakdown of points. Spearman correlations were also calculated to evaluate the relationship between match outcomes in both stages. Statistical significance was considered when p < 0.05. A comparison of match outcomes may reveal that the performance between teams was balanced. Furthermore, the Spearman correlations suggest that the number of tries is highly related to the points scored in the both stages. The final stage of the Japan Rugby Top League 2018 did not focus on a safety-first approach.